FROM THE HISTORY OF WAQF PROPERTY IN TURKESTAN - S. D. Boltabayev (Modern American Journals, 2025)
This article provides information on the existing Waqf properties in Turkestan and the school and madrasas in their composition, the income received by mosques, Waqf properties, the construction history of madrasas and the composition of the subjects taught in them.
Keywords: Waqf properties, schools, madrasas, mosques, structure of waqf documents, Islamic religion, general governorship, decrees, teaching of religious and secular sciences.